PROBLEMATIKA DAN SOLUSI KREDIT MACET KREDIT USAHA RAKYAT (KUR) PADA BANK X (Jurnal Riset Manajemen dan Akuntansi, 2022)
This research is motivated by the problems that occur in banks, namely bad loans, this is due to the lack of cooperative debtors in completing their installment obligations and mistakes made by the bank in conducting debtor surveys and credit analysis. The method used in this study is a qualitative approach, through interviews with employees of Bank X. The conclusion of the resolution of the problem of bad loans in this study is by intensive collection when the debtor is in arrears in installments. Bank X will also restructure or reschedule the debtor's credit (there is a change in the term and the amount of installments) this is intended so that debtors can have the ability to pay installments smoothly. When the debtor is really unable to make repayments or installment payments, the bank will sell the assets and collateral/collateral from the debtor.